Avaliação dos distúrbios do movimento em pacientes com doenças desmielinizantes - Silva, Carolina Candeias da [UNIFESP] (2017)
Objective: To describe the prevalence and characteristics of movement disorders in patients with MS (multiple sclerosis) and NMOSD (neuromyelitis optica spectrum disorder) followed at the Neuroimmunology clinic at Universidade Federal de São Paulo. In addition, to investigate the association between MS, NMOSD, disability, movement disorders and quality of life. Methods: A cross-sectional study of patients with demyelinating diseases was conducted from June 2015 to September 2016. Patients aged 18 years or older, without significant cognitive impairment and with diagnostic criteria for MS or NMOSD were eligible. We evaluated 268 patients, 15 were excluded. The main exclusion criteria was other possible cause related with the movement disorder. Patients were evaluated with interview and physical exam by a neurologist specialist in movement disorder. We used the following tools: the EDSS (Expanded Disability Status Scale), the Fahn Tolosa and Marín tremor rating scale, the modified Ashworth scale, for assessment of spasticity, and EuroQoL- 5 Dimensions questionnaire, for analysis of quality of life. Results: From 253 patients included, 26% presented with movement disorders. The majority of the patients was female (74.3%), with a mean age of 40.36 years (SD = 11.74). The median EDSS score of included patients was 2.5 with interquartile range of 1.0- 6.0. Paroxysmal dystonia (n=32) was the most common movement disorder, followed by tremor (n=27). The prevalence of tremor in MS was 12.5% and intention tremor was the most common (82%). Patients with MS and low EDSS score (<4,0), compared to NMOSD, have fewer movement disorders. Paroxysmal dystonia was strongly associated to NMOSD diagnosis (OR=22.07, 95%CI=2.56 - 189.78; p=0.005). The mean of utility scores of quality of life was 0.58 (SD=0.26), patients with MS have 0.15 points higher on average than patients with NMOSD, and patients with movement disorders have 0.083 points lower than those without them. Conclusion: The presence of movement disorders in patients with demyelinating diseases seems to be related with severity and progression of the disease. Paroxysmal dystonia is significantly more associated with NMOSD, and may be a clinical marker of this. Intention tremor was the most common movement disorder in MS. It has been demonstrated an impact on the quality of life of patients with demyelinating diseases and movement disorders.